SKEMA INSENTIF : PRESEPSI GENERASI Z DI SURAKARTA - Dewinda, Mutty Claudia; Candrakusuma, Desy Amalia; R, Mandasari (ITB AAS Indonesia Surakarta, 2025)
Abstract This study aims to examine and provide empirical evidence on the effect of incentive schemes on employee performance. The study used bonuses, allowances, flexible work arrangements, and career development as components of the company's incentive schemes to employees. The unique characteristics of Generation Z, as the main drivers in optimizing Indonesia's demographic bonus, are considered in this research. This is a quantitative study with a sample comprising 148 Generation Z individuals in Surakarta. The results show that bonuses positively and significantly effect on employee performance. Allowances have a negative and significant effect on employee performance. Furthermore, flexible work arrangements positively and significantly effect on employee performance, while career development have no effect on employee performance. Â Keywords : Bonus, Allowance, Flexible Work Arrangements, Career Development, Employee Performance.